HOLMIUM LASER IN TRANSURETRAL TREATMENT OF LOWER URINARY TRACT STONES (World Bulletin of Public Health, 2022)
Urolithiasis is one of the most common pathologies among urological diseases and occurs in at least 1-3% of the population, most often in people of working age - 20-50 years. Urolithiasis is recorded in 10% of the population and has an annual increase.